The Impact of China's Ageing Population on Consumption Structure - Mohd, Saidatulakmal; Du, Xuyang (The Malaysian Journal of Social Administration, 2025)
The rapid development of population ageing makes China a unique subject for study relative to other developed countries with high levels of ageing. Meanwhile, income inequality widens as China's economy grows, making it a major social issue that needs to be addressed. This study evaluates the impact of ageing on income inequality in China's 31 provinces by ANOVA analysis. Panel data is collected from NBS from 2010 to 2020. The estimation results indicate that population ageing tends to widen income inequality during 2010-2020 in China and this impact has a significant time lag.